TUBUH DAN PENUBUHAN DALAM CERPEN SRI SUMARAH KARYA UMAR KAYAM: TELAAH PASCAKOLONIAL DAN FEMINISME - Trisna Gumilar (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Writing a text with feminist perspective isn’t talk about moral (that intentionally build with social discourse that havepatriarchal perspective), but more based on women speaking opportunity, giving space to woman to express her desire, her need, and herright with the result she able to became subject on her life. Sri, figure on Sri Sumarah short story by erpen Sri Sumarah Umar Kayam,Karya Umar Kayamhappy with her role as kanca wingking (backside partner), at the end cant continue her role as second sex. She have tonegotiate and adapt with new environment, new condition, and new society, even her old culture still have strong grasp. Sri cannotanymore submit to society’s eyes. She negotiates with herself and with her body